Standardising the administration of joint injections across the Wolverhampton NHS Trust: a service improvement project in rheumatology through the lens of medical education - Hirushi Jayasekera; Tamaraudubamo Agunbiade; S. Venkat Chalam (Future Healthcare Journal)
Introduction: The Rheumatology Resident Doctors' Forum identified a pressing need to standardise steroid injection training due to varying experience and confidence levels among resident doctors. Many expressed a strong interest in learning injection techniques but faced barriers in accessing training and achieving formal competency. Addressing this gap had the potential to enhance service delivery, support professional development and reduce patient wait times. General practice trainees also highlighted the value of joint injection skills in primary care, helping to alleviate pressure on rheumatology services.The Dreyfus model of skill acquisition describes five levels of competency in skill development, ranging from ‘novice’ to ‘competent’ and eventually ‘expert’.1 The model shows how individuals progress from rule-based, analytical thinking to experience-driven mastery of a skill.1 A recent study demonstrates that structured training can enhance competency in procedural skills, such as joint injections.2 Methods: A SMART aim was used to design learning outcomes. Fourteen applicants were selected at random. Pre-course surveys collected quantitative and qualitative data on performance challenges, confidence, and baseline knowledge. Process mapping (Fig 1) and radar diagrams (Fig 2) highlighted gaps for intervention. Four trained rheumatology doctors, supervised by a consultant, led a teaching program. Virtual meetings guided plan–do–study–act (PDSA) cycles and driver diagrams to ensure constructive alignment.The goal was to advance learners from the Dreyfus level of ‘Novice 1’ to 'Competent 1’. The course, conducted in the clinical suite, used training mannikins of knees and shoulder joints, providing real-time feedback. Teaching combined interactive lectures, small-group sessions and individualised feedback. Formative assessments maximised educational impact. Post-course data were compared to baseline, with quality improvement (QI) sustainability tools used to draw portal diagrams, highlight improvement gains and discuss long-term impacts of the project. Results and discussion: Initially, 50% of participants were novices, with none having ever injected a shoulder joint. Confidence in consenting patients increased from 14% to 100% post-course. 64% of participants were unfamiliar with medications used for injections, while 28.6% were unsure of the evidence base. Post-course, both categories improved to 100%.Additionally, 43% initially lacked confidence in clinical decision-making regarding safe joint injection. There was a 100% increase in overall confidence surrounding decision-making (43% ‘strongly confident’ and 57% ‘confident’). All doctors passed the criterion-referenced standard assessment, acquiring formal recognition of skills in their portfolios. The course was oversubscribed and received excellent feedback.QI tools, including radar diagrams, process mapping, and PDSA cycles, had a crucial role in refining training and driving measurable improvements. The structured application of QI methodology successfully upskilled doctors, advancing them from 'Novice' to 'Competent'. Simulation-based learning, combined with real-time feedback, proved to be a highly effective strategy for accelerating skill development while enhancing clinical decision-making and confidence. By integrating this training into departmental inductions, the initiative ensured sustainability and continuous professional development, benefiting both individual practitioners and the wider healthcare service. Conclusion: The project led to significant improvements in confidence and competency. It demonstrated sustainability through reproducibility and was incorporated into the rheumatology departmental induction. Positive feedback highlights the course’s broader applicability in QI-driven medical training.